Resistance training in musculoskeletal rehabilitation: a systematic review - Kristensen, J.; Franklyn-Miller, A. (British Journal of Sports Medicine, 2012)
Objective To review the efficacy of resistance training (RT) as a therapeutic modality in various musculoskeletal conditions.Design Systematic review.Subjects Data from 1545 rehabilitation patients who had participated in structured RT programmes were included into the review. The total number of patients was composed of separate musculoskeletal conditions—chronic low back pain (CLBP) (549), tendinopathy (299), knee osteoarthritis (433), anterior cruciate ligament reconstruction (189) and hip replacement surgery (75).Results Evidence suggests that RT can increase muscle strength, reduce pain and improve functional ability in patients suffering from CLBP, knee osteoarthritis, and chronic tendinopathy and those under recovery after hip replacement surgery.Conclusion RT can be used successfully as a therapeutic modality in several musculoskeletal conditions, especially those of a chronic variety. Although the exact application of training intensity and volume for maximal therapeutic effects is still unclear, it appears that RT guidelines, which have proven effective in a healthy population, can also be successfully applied in a rehabilitation context.